Battlefield Tourism in South Africa with Special Reference to Isandlwana and Rorke's Drift KwaZulu-Natal - Fairer-Wessels, Felicite A. (University of Pretoria, 2013)
Dissertation (MPhil (Tourism Management))--University of Pretoria, 2007.